Molecular and Ionic Dipole Effects on the Electronic Properties of Si-/SiO2-Grafted Alkylamine Monolayers - Gankin, Alma; Sfez, Ruthy; Mervinetsky, Evgeniy; Buchwald, Jorg; Dianat, Arezoo; Sandonas, Leonardo Medrano; Gutierrez, Rafael; Cuniberti, Gianaurelio (Giovanni); Yitzchaik, Shlomo (ACS Applied Materials and Interfaces, 2017)
In this work, we demonstrate the tunability of electronic properties of Si/SiO2 substrates by molecular and ionic surface modifications. The changes in the electronic properties such as the work function (WF) and electron affinity were experimentally measured by the contact potential difference technique and theoretically supported by density functional theory calculations. We attribute these molecular electronic effects mainly to the variations of molecular and surface dipoles of the ionic and neutral species. We have previously shown that for the alkylhalide monolayers, changing the tail group from Cl to I decreased the WF of the substrate. Here, we report on the opposite trend of WF changes, that is, the increase of the WF, obtained by using the anions of these halides from Cl- to I-. This trend was observed on self-assembled alkylammonium halide (-NH3+ X-, where X- = Cl-, Br-, or I-) monolayer-modified substrates. The monolayer's formation was supported by ellipsometry measurements, X-ray photoelectron spectroscopy, and atomic force microscopy. Comparison of the theoretical and experimental data suggests that the ionic surface dipole depends mainly on the polarizability and the position of the counter halide anion along with the organization and packaging of the layer. The described ionic modification can be easily used for facile tailoring and design of the electronic properties Si/SiO2 substrates for various device applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: contact potential difference; DFT; ionic dipole; molecular dipole; self-assembled monolayer; work function